Itemizes East Java Heritage Tourism Nexus: In Consort of “Pentahelix” Method via Didactic Vicissitudes Adherence - Bagus Firmansyah, Sultan (Samarinda State Polytechnic, 2021)
As 21st century and/ or urban spots skyrocketing nonstop, particularly at East Java, a bunch of anti-outmoded places’ quantity exceeds both heritage and monumental tourism sites. Attempting archaic didactic principles in familiarizing pupils with heritage tourism equals nothing, nor is (using) printed book; a fine-tech focal notion shall be done. This research heads renewal worth noting idea, it’s antihelix; the method coalesces Academician, Business, Community, Government, and Media abbr. ABCGM, thus, foregoing fifth stakeholders can emerge a distinct tactic of transferring heritage tourism science to students. It can by locating learners’ interests via sophisticated 5.0 features e.g. Virtual Reality/ VR, Augmented Reality/ AR, 3D Demo, etc. To do so, pupils’ endeavour forecast is aimed at history-savvy, minifying heritage unawareness, and nurturing annals of historic sites. A resilient historic site encompasses Edu-tourism importance, with a view from within. This research has ≤ 38 respondents (from 29 regencies and 8 cities in East Java province) whose essence about monumental tourism preservation weightiness.